2016
DOI: 10.21162/pakjas/16.2226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aminoethoxyvinylglycine and Naphthaleneacetic Acid on Ethylene Biosynthesis, Pre-Harvest Fruit Drop and Fruit Quality of Apple

Abstract: Cultural control of pre-harvest drop has relied upon plant growth regulators. To investigate the effects of plant growth regulators on pre-harvest drop and fruit quality, 150, 300 and 600 mg L -1 aminoethoxyvinylglycine (AVG) and 20 mg L -1 NAA were sprayed to 'Red Chief' apple trees at 4 week before anticipated harvest date. Untreated trees were kept as control. Results revealed that all AVG treatments increased the fruit removal force and significantly delayed pre-harvest drop and fruit maturity. Pre-harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…3i), however, a benefit was obtained by applying NAA plus Ethephon in the preharvest by standardizing fruit maturation (Brackmann et al 2014). Ozkan et al (2016) verified less flesh firmness of 'Red Chief ' apple in treatment with application of 20 mg•L -1 of NAA compared whit different AVG concentrations, in the two evaluated years, which is in agreement with the results of this study.…”
Section: Postharvest Quality Of 'Brookfield' Applesupporting
confidence: 89%
“…3i), however, a benefit was obtained by applying NAA plus Ethephon in the preharvest by standardizing fruit maturation (Brackmann et al 2014). Ozkan et al (2016) verified less flesh firmness of 'Red Chief ' apple in treatment with application of 20 mg•L -1 of NAA compared whit different AVG concentrations, in the two evaluated years, which is in agreement with the results of this study.…”
Section: Postharvest Quality Of 'Brookfield' Applesupporting
confidence: 89%
“…Increased levels of WL during storage could also be a result of increased rates of respiration [ 65 ]. Previous reports have also indicated that AVG improved fruit firmness in sweet cherry [ 13 ], pear [ 21 ], and apple [ 12 , 22 ]. In addition, SA-treated fruit recorded a small reduction in WL ( Figure 2 ), which was associated with improved fruit firmness ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 98%
“…Previous findings revealed that PFD is diminished with delayed fruit ripening using AVG that reduced ethylene biosynthesis via the inhibition of ACC synthase activity [ 22 , 60 , 61 ]. It was reported that spraying apple trees with AVG four weeks before harvest delayed the fruit ripening rate and decreased PFD by 50% [ 12 ]. Preharvest application of SA also decreased PFD [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations